Genome-Wide Analysis Reveals Hypoxic Microenvironment Is Associated With Immunosuppression in Poor Survival of Stage II/III Colorectal Cancer Patients - Chen, Yu-feng; Yu, Zhao-liang; Lv, Min-yi; Zheng, Bin; Tan, Ying-xin; Ke, Jia; Liu, Xuan-hui; Cai, Ze-rong; Zou, Yi-feng; Lan, Ping; Wu, Xiao-jian; Gao, Feng (Frontiers in Medicine, 2021)
Background: Hypoxia is associated with a poorer clinical outcome and resistance to chemotherapy in solid tumors, identifying hypoxic related colorectal cancer (CRC) and revealing its mechanism are important. The aim of this study was to assess hypoxia signature for predicting prognosis and analyze relevant mechanism. Methods: Patients without chemotherapy were selected for the identification of hypoxia-related genes (HRGS). A total of 6 independent datasets included 1,877 CRC patients were divided into a training cohort and two validation cohorts. Functional annotation and analysis were performed to reveal relevant mechanism. Results: A 12-gene signature was derived, which was prognostic for stage II/III CRC patients in two validation cohorts (TCGA, n=509, HR=2.14, 95%CI=1.18-3.89, P=0.01; meta-validation, n=590, HR=2.46, 95%CI=1.59-3.81, P<0.001). High hypoxic risk was correlated with worse prognosis in CRC patients without adjuvant chemotherapy (HR=5.1, 95%CI=2.51-10.35, P<0.001). After integrated with clinical characteristics, HRGS remained as an independent prognostic factor in multivariate analysis. Furthermore, enrichment analysis found that anti-tumor immune response was suppressed in the high hypoxic group. Conclusions: HRGS is a promising system for estimating disease-free survival of stage II/III colorectal cancer patients. Hypoxia tumor microenvironment may via inhibiting immune response to promote chemoresistance in stage II/III colorectal cancer patients.